ANALYZE THE DIGESTIBILITY OF DRY MATTER AND ORGANIC MATTER CASSAVA CLONES® BYPRODUCTS ON THE WEANING LOCAL MALE SHEEP - Berry Okta Libra (Universitas Sumatera Utara, 2014)
This study aims to analyze the digestibility of dry matter and organic matter cassava clones by-products on the weaning local male sheep. The experiment was conducted at Laboratory of Animal Biology, Faculty of Agriculture Livestock Studies Program University of Sumatra Utara in September to December 2013. The design used in this research is completely randomized design ( CRD ) with 3 treatments and 4 repications. The design consist of P0 : ( 100 % grass ), P1 ( 50 % grass and 50 % cassava by product ) and ( P2 100 % cassava by product ). The results showed the average digestibility dry matter 47,00(%), 52,43(%) and 54,65(%) respectively. Organic matter were 50,19 (%), 52,74 (%) and 54,81(%) respectively. Statistical test results showed that feeding cassava were very significant effect on the digestibility of dry matter and organic matter .The conclusions of this study the cassava by product digestibility of dry matter and organic matter better than digestibility of dry matter and organic matter of grass, so cassava by products can be use as an alternative feed. Keywords : Cassava , By product , Local sheep male .